Th2 cytokines and asthma — The role of interleukin-5 in allergic eosinophilic disease - Greenfeder, Scott (BioMed Central, 2001)
Interleukin-5 is produced by a number of cell types, and is responsible for the maturation and release of eosinophils in the bone marrow. In humans, interleukin-5 is a very selective cytokine as a result of the restricted expression of the interleukin-5 receptor on eosinophils and basophils. Eosinophils are a prominent feature in the pulmonary inflammation that is associated with allergic airway diseases, suggesting that inhibition of interleukin-5 is a viable treatment. The present review addresses the data that relate interleukin-5 to pulmonary inflammation and function in animal models, and the use of neutralizing anti-interleukin-5 monoclonal antibodies for the treatment of asthma in humans.